When a 'Waterhole' Is Full of Dung: An Illustration of the Importance of Environmental Evidence for Refining Archaeological Interpretation of Excavated Features. (25th January 2019) - Buckland, P. I.; Buckland, P. C.
Abstract : Prehistoric field systems sometimes encompass excavated, pit‐like features which are difficult to classify due to the complex stratigraphies resulting from reuse, infilling and collapse. They are frequently classified as wells and watering holes, but other potential uses for excavated depressions are rarely cited. We argue the need for environmental archaeology in the interpretation of features of this nature, and present a case study from a Bronze Age site at Pode Hole, near Peterborough (UK), where fossil insect material clearly contradicts the archaeological interpretation. We present empirical evidence for a sealed context filled with dung which cannot be interpreted as a water source. This evidence strongly contrasts with other superficially similar features at the site.